GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 7757 species occurrences available in GBIF matching the query: TaxonKey: Puma concolor (Linnaeus, 1771). The dataset includes 7757 records from 122 constituent datasets: 269 records from NatureServe Network Species Occurrence Data. 3 records from Western Australian Museum provider for OZCAM. 24 records from Colección nacional de zoología. 27 records from Paleobiology Database. 3 records from Mammal collection of National Museum of Nature and Science. 6 records from UWYMV Mammal Collection (Arctos). 42 records from SBMNH Vertebrate Zoology. 2 records from Mammal collection, Natural History Museum, University of Oslo. 14 records from NYSM Mammals. 905 records from MSB Mammal Collection (Arctos). 7 records from Mammals Specimens. 112 records from University of California Museum of Paleontology. 7 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 182 records from AMNH Mammal Collections. 1745 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 2 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 16 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 3 records from NMMNH Mammal. 2 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 3 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 147 records from iNaturalist research-grade observations. 57 records from TTU Mammals Collection. 149 records from New Mexico Biodiversity Collections Consortium database. 4 records from University of Ghent - Zoology Museum - Vertebratacollectie. 1 records from condoncollection. 49 records from Macaulay Library Audio and Video Collection. 2 records from Mamíferos laguna El Tinije. 12 records from Mammal specimens. 2 records from naturgucker. 453 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 63 records from CAS Mammalogy (MAM). 19 records from Collection Mammalia SMF. 53 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from (UTC) University of Tennessee Mammals Collection. 110 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 108 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 1 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 29 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 32 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 9 records from CCBER Mammalogy Collection. 6 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 7 records from CHAS Mammalogy. 2 records from WNMU Mammal Collection (Arctos). 25 records from Database Schema for UC Davis Wildlife museum. 52 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 13 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 12 records from Geographically tagged INSDC sequences. 37 records from Colección de Mastozoología. 1 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 91 records from UCM Mammal Collection (Arctos). 25 records from HSU Wildlife Mammals. 1 records from Queensland Museum provider for OZCAM. 13 records from Mammals housed at MHNG, Geneva. 2 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 21 records from CRCM Vertebrate Collection. 30 records from Naturalis Biodiversity Center (NL) - Mammalia. 23 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 7 records from UAM Mammal Collection (Arctos). 3 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 16 records from LSUMZ Mammals Collection. 2 records from CUMV Mammal Collection (Arctos). 107 records from Animal Sound Archive. 2 records from IIAPPoa. 28 records from UCLA Donald R. Dickey Bird and Mammal Collection. 16 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 8 records from MLZ Mammal Collection (Arctos). 49 records from Cowan Tetrapod Collection - Mammals. 3 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 1 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 1 records from Lund Museum of Zoology (MZLU). 7 records from South Australian Museum Australia provider for OZCAM. 25 records from CSUC Vertebrate Collection. 8 records from UMZC Zoological Specimens. 1 records from Colección de Mamíferos del Centro Nacional Patagónico. 28 records from RBINS collections. 1 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1 records from Zoology (Museum of Evolution - Uppsala). 202 records from Plan de vertebrados de la Patagonia. 3 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 2 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 3 records from MVZ Hildebrand Collection (Arctos). 53 records from PSM Vertebrates Collection. 26 records from University of Alberta Mammalogy Collection (UAMZ). 5 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 12 records from Fundación Miguel Lillo - Colección Mamíferos. 59 records from UWBM Mammalogy Collection. 330 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 8 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 38 records from UTEP Vertebrates. 195 records from MVZ Mammal Collection (Arctos). 13 records from CNMA/Colección Nacional de mamíferos. 56 records from LACM Vertebrate Collection. 2 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 21 records from UMMZ Mammal Collection. 1 records from ISU Mammals. 3 records from FHSM Mammals Collection. 72 records from Mammalogy Collection - Royal Ontario Museum. 122 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 827 records from NMNH occurrence DwC-A. 6 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 17 records from UNSM Vertebrate Specimens. 3 records from Ibaraki Nature Museum, Mammals collection. 1 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 6 records from Colección Mastozoológica de la Universidad Industrial de Santander. 58 records from DMNS Mammal Collection (Arctos). 12 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 4 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 18 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 9 records from NCSM Mammals Collection. 22 records from Australian Museum provider for OZCAM. 2 records from MfN - Fossil vertebrates IV. 1 records from Naturhistorisches Museum Mainz, Zoological Collection. 23 records from Natural History Museum (London) Collection Specimens. 3 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 3 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 56 records from Museum of Comparative Zoology, Harvard University. 28 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 78 records from KUBI Mammalogy Collection. 1 records from Colección de moldes endocraneanos del CENPAT.
Keywords: GBIF; biodiversity; species occurrences